2014
DOI: 10.1021/es5017125
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Reduction of U(VI) under Alkaline Conditions: Implications for Radioactive Waste Geodisposal

Abstract: Although there is consensus that microorganisms significantly influence uranium speciation and mobility in the subsurface under circumneutral conditions, microbiologically mediated U(VI) redox cycling under alkaline conditions relevant to the geological disposal of cementitious intermediate level radioactive waste, remains unexplored. Here, we describe microcosm experiments that investigate the biogeochemical fate of U(VI) at pH 10-10.5, using sediments from a legacy lime working site, stimulated with an added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 51 publications
3
44
0
Order By: Relevance
“…Interestingly, sulfate removal was also observed by day 7, suggesting sulfate reduction was occurring in these systems (Fig.1). This is in contrast to systems maintained at pH 10 ( Williamson et al, 2014), where sulfate reduction is energetically unfavourable (Rizoulis et al, 2012), and highlights the potential for localized acidification due to biogeochemical processes in radioactive waste disposal. In the systems with added Fe(III), complete nitrate removal occurred by day 3 and nitrite concentrations then increased (Fig.…”
Section: Biogeochemistry In Sediment Microcosmsmentioning
confidence: 75%
See 1 more Smart Citation
“…Interestingly, sulfate removal was also observed by day 7, suggesting sulfate reduction was occurring in these systems (Fig.1). This is in contrast to systems maintained at pH 10 ( Williamson et al, 2014), where sulfate reduction is energetically unfavourable (Rizoulis et al, 2012), and highlights the potential for localized acidification due to biogeochemical processes in radioactive waste disposal. In the systems with added Fe(III), complete nitrate removal occurred by day 3 and nitrite concentrations then increased (Fig.…”
Section: Biogeochemistry In Sediment Microcosmsmentioning
confidence: 75%
“…The pyrosequencing run was performed at The University of Manchester sequencing facility using a Roche 454 Life Sciences GS Junior system. Details of the PCR procedure and pyrosequencing analysis have been previously outlined (Williamson et al, 2014). The pyrosequencing reads from this study will be deposited in the NCBI Sequence Read Archive (SRA).…”
Section: S Rrna Gene Amplicon Pyrosequencing and Data Analysismentioning
confidence: 99%
“…A vast number of dissimilatory iron reducing bacteria have been identified in soil environments (Wang et al 2009;Yuan et al 2016), and almost all microorganisms capable of reducing Fe(III) can also reduce humic substances (including AQDS) (Lovley et al 1999). It was found that humic substances including AQDS promoted the reduction of Fe(III) (oxyhydr)oxides driven by alkaliphilic bacteria isolated from extreme environments (pH 10.0 microbial fuel cells) and in uranium-contaminated sediments of pH 10.0-10.5 (Ma et al 2012;Wu et al 2013;Williamson et al 2014). The alkaliphilic bacteria could not represent microorganisms in natural soils and it is still ambiguous whether humic substance-mediated Fe(III) reduction is pervasive by common microorganisms in alkaline soils.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it was shown that a clear succession of electron acceptor utilization existed in alkaline microcosm cultures up to pH 11, as rapid nitrate reduction was followed by slower soluble Fe(III)-citrate, insoluble Fe(III)-oxyhydroxide, and sulfate reduction (Rizoulis et al 2012). Further sediment microcosm studies from our group have also shown that alkaline bioreduction of Fe(III)-oxyhydroxide can lead to the formation of magnetite (Williamson et al 2013) and that microbially mediated reduction of U(VI) can occur at pH 10 (Williamson et al 2014).…”
Section: Potential For Metal Reduction At Alkaline Phmentioning
confidence: 74%